A Multi‐crosslinking Nanocapsule‐Based Serial‐Stimuli‐Responsive Leakage‐Free Drug‐Delivery System In Vitro. Issue 56 (9th September 2019) - Liu, Yazhou; Shen, Tianjiao; Gao, Congcong; Abdulhadi El‐Ali, H. A.; Gao, Na; Yang, Chunlei; Zhang, Rubo; Jing, Jing; Zhang, Xiaoling
Abstract: As some stimuli utilized in conventional drug delivery systems can also be found in normal cells, it is inevitable that encapsulated drugs escape from carriers into normal cells. Based on mutual interactions among proteins, polyphenol compounds, and metal ions, we developed a serial‐stimuli‐responsive drug delivery system. With multi‐crosslinking structure, nanocapsules can maintain the integrity of the framework, even with a certain amount of stimuli present, and eventually reach tumor cells to initiate apoptosis, and protect normal cells from being damaged. Meanwhile, the fluorescence of DOX will be quenched when encapsulated in nanocapsules. This property means that the DOX that is released from nanocapsules can be monitored in real‐time based on the recovery of fluorescence. These versatile nanocapsules exhibit great potentials to treat cancer. Abstract : Serial stimuli : Based on the different relations among various stimuli, multi‐stimuli‐responsive drug delivery systems can be divided into two distinct types: parallel mode and serial mode (see figure). Their working ways are just like parallel and serial circuits.